Bridging the ICD11 and the DSM-5 personality disorders classification systems: The role of the PID5BF + M - Pires, Rute; Henriques-Calado, Joana; Sousa Ferreira, Ana; Gama Marques, João; Ribeiro Moreira, Ana; Barata, Bernardo C.; Paulino, Marco; Gonçalves, Bruno (Frontiers in Psychiatry, 2023)
Considering the similarity of both the ICD-11 Classification of Personality Disorders and the DSM-5 Alternative Model of Personality Disorders (AMPD) classification systems, it would be helpful to clinicians if these two systems were harmonized. With this goal in mind, the PID5BF+M, an algorithm that assesses the DSM-5 and ICD-11 six trait domains and 18 facets, was developed and has proven to adequately characterize the ICD-11 trait domains by means of DSM-5 trait facets. The current study compares a community sample (N = 282, Mage = 48.01, 53.2% females) with a PD sample (N = 131, Mage = 42.66, 45.0% females) along with the PID5BF+M, the LPFS-SR and the PID-5. Given that the PID5BF+M total can be seen as a measure of the level of personality dysfunction, strong relations between the PID5BF+M total and the LPFS-SR total are expected. Strong relations between the trait specifiers measured by the PID5BF+M and the PID-5 are also expected. Finally, the community and clinical samples are expected to differentiate by means of the dimensions assessed through the three afore-mentioned measures. The Spearman rank-order correlation coefficient was used to measure the strength and direction of associations between the PID5BF+M total and the LPFS-SR total and between the PID5BF+M and the PID-5 traits. Group differences were explored using the Mann-Whitney U test for independent samples. As expected, there were strong, significant, and positive relations between the measures. Moreover, the PD group showed significantly higher scores than the community group in all the variables. Although this study has limitations, its findings sustain that the PID5BF+M has potential to assess the severity of personality disfunction and to characterize the stylistic features of PD as they are conceived by both the ICD-11 and the DSM-5. Although more research is needed regarding the convergent validity of the PID5BF+M, this new test contributes to the harmonization of both systems and to parsimony in the assessment of PD, which is the main objective of clinical practice.